VARIABILITY OF THE TOPOGRAPHICAL ANATOMY OF THE MAXILLARY ARTERY - LITERATURE REVIEW - Diana Loreta Păun; Maria Justina Roxana Vîrlan; Elena Nicoleta Bordea; Angelo Pellegrini; Ramona Ionela Truţă; Roxana Victoria Ivaşcu; Alexandru Poll; Suzana Carmen Cismaş; Vanda Roxana Nimigean; Victor Nimigean (Romanian Society of Oral Rehabilitation, 2021)
The maxillary artery (MA) is the main vascular source for the maxillary and mandibular tooth-gum-alveolar bone units, running adjacent to the lateral pterygoid muscle. The purpose of this review is to bring evidence-based knowledge on the topography and trajectory variations of the MA in the infratemporal region, with emphasis on clinically relevant findings. The MA is the most important vascular element in the infratemporal region due to its relationships with the nerve branches encountered at this level. The variability of the topographical relationships of the MA within the infratemporal region can lead to complications in oral and maxillofacial surgery. Knowledge of the anatomical variations of the MA contributes to the prevention and reduction of a wide variety of surgical complications